2022
DOI: 10.1186/s43058-022-00325-y
|View full text |Cite
|
Sign up to set email alerts
|

How low can you go? Examining the effects of brief online training and post-training consultation dose on implementation mechanisms and outcomes for measurement-based care

Abstract: Background Initial training and ongoing post-training consultation (i.e., ongoing support following training, provided by an expert) are among the most common implementation strategies used to change clinician practice. However, extant research has not experimentally investigated the optimal dosages of consultation necessary to produce desired outcomes. Moreover, the degree to which training and consultation engage theoretical implementation mechanisms—such as provider knowledge, skills, and at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Both groups reported similar data collection rates using the MFS, and higher rates of measure collection compared to rates of providing feedback or using MFS data to inform changes to treatment course. Previous MBC studies show similar trends: using data and adjusting treatment based on data is often the most difficult practice to change in implementation [ 47 , 76 78 ]. Yet, even adjusting for agency, Higher MFS participants reported significantly higher rates of providing feedback based on the MFS, compared to the Lower MFS participants.…”
Section: Discussionmentioning
confidence: 77%
“…Both groups reported similar data collection rates using the MFS, and higher rates of measure collection compared to rates of providing feedback or using MFS data to inform changes to treatment course. Previous MBC studies show similar trends: using data and adjusting treatment based on data is often the most difficult practice to change in implementation [ 47 , 76 78 ]. Yet, even adjusting for agency, Higher MFS participants reported significantly higher rates of providing feedback based on the MFS, compared to the Lower MFS participants.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to appointing specific staff members to be responsible for tool administration and adjusting electronic documentation systems, staff should have access to initial training as well as ongoing consultations to confirm procedures for administration, documentation, and interpretation of results. The combination of training and follow-up consultations has been previously found effective for supporting the uptake of evidence-based interventions and assessments ( 53 , 54 ), particularly in the community setting. Lastly, of the available data our partner agency's staff collected from clients beyond May 2021, we identified that clients had unmet needs, especially in the domains of function and mobility, that could not be addressed through home-delivered meal services alone.…”
Section: Discussionmentioning
confidence: 99%
“…Recommending more training appears to be a simple solution. However, implementation research points to the complex challenges and lack of success in practice change with this approach (Evans et al , 2022; Lyon et al , 2022; Lyon et al , 2011). It is well known that transforming systems and processes is needed to change practice.…”
Section: Discussionmentioning
confidence: 99%